Peran Kimia Lingkungan dalam Konservasi Sumber Daya Alam - Hasan, Haslinda (Jurnal Ilmiah Multidisiplin Amsir, 2023)
Environmental problems are a very important topic and an interesting issue to discuss both in Indonesia and abroad. Technological developments, in the industrial world and population growth have an important role in influencing environmental problems. Improvements in technology and industry have played a significant role in the implementation of development, as a consequence the amount of raw materials and industrial waste has increased. This has an impact on pollution and environmental damage. The important role of environmental chemistry in maintaining the sustainability of natural resources and the environment. Environmental chemistry plays a significant role in understanding, preventing, and addressing environmental problems faced by humans.